COMPARISON OF THE REGULATIONS ON RECIDIVIST JUVENILES IN INDONESIA, NORWAY, AND THAILAND - Arfan Kaimuddin (Legal Standing : Jurnal Ilmu Hukum, 2019)
As the future leaders of the nation, children must obtain protection from all sides. This protection is also needed when children become recidivists. The Indonesian Criminal Code states that for recidivists, the punishment in a repeat of criminal action will be added by a third. Surely, this will bring much loss to the future of the children who repeated actions of criminality (recidivist juveniles). This research is aimed to analyze and to describe how the regulations on repeated criminal action are for juveniles in Indonesia, Norway, and Thailand. This is a juridicial-normative research, with constitutional and comparison approaches. Provisions of the Norway Criminal Code Article 61 and provisions of the Thailand Criminal Code Article 94 have some similarities. It is stated that the repeated action of crime is only given to those who repeated the criminal action who are above 18 and 17 years of age.